2017
DOI: 10.2147/jpr.s154038
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic osteoarthritis-induced persistent mechanical hyperalgesia in a rat model of anterior cruciate ligament transection plus a medial meniscectomy

Abstract: BackgroundOsteoarthritis (OA) is a degenerative joint disease characterized by progressive cartilage degeneration, subchondral bone changes, osteophyte formation, and synovitis. A major symptom is pain that is triggered by peripheral and central changes within the pain pathways. Some surgery-induced joint instability rat models of OA were described to mimic traumatic OA. Several behavioral tests were developed to access OA-induced pain. However, follow-up in most studies usually only occurred for about 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Finally, the chronicity characteristics of KOA may explain the absence of a cryotherapy effect on both skin temperature and swelling of the knee joint. There were also no changes in thermal hyperalgesia in the KOA model, which is supported by previous studies of the post-traumatic KOA model 47,48 . Behavioral changes commonly reported in the literature involve the assessment of other parameters, such as gait adaptations, mechanical hyperalgesia, mechanical allodynia and weight-bearing asymmetries.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the chronicity characteristics of KOA may explain the absence of a cryotherapy effect on both skin temperature and swelling of the knee joint. There were also no changes in thermal hyperalgesia in the KOA model, which is supported by previous studies of the post-traumatic KOA model 47,48 . Behavioral changes commonly reported in the literature involve the assessment of other parameters, such as gait adaptations, mechanical hyperalgesia, mechanical allodynia and weight-bearing asymmetries.…”
Section: Discussionsupporting
confidence: 90%
“…This result corroborates a recent study that found reduced pain threshold associated with muscle weakness after ACLT 53 . Another recent study showed the presence of persistent mechanical hyperalgesia in a KOA model 54 . Our results strengthen the evidence that pain is related to the inflammatory and neuromuscular changes observed in the KOA.…”
Section: Discussionmentioning
confidence: 94%
“…Chemical-OA and surgery-OA models may induce different degrees of pain over time. Multiple methods have been used to analyze pain behaviors 32 ; the Von Frey filament test and open field test are generally used to assess these. At the later stages of MIAinduced OA, the damage to exposed subchondral bone and synovia resembles human OA and is related to joint pain.…”
Section: Discussionmentioning
confidence: 99%